Produksi Enzim lakase Oleh Jamur Tricoderma Asperellum Lbkurcci Secara Fermentasi Padat Pada Bioreactor Tray - Muhamad Fajri; Sri Helianty; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Laccase enzyme is classified as oxidoreductase enzyme; i.e. an enzyme that can oxidize phenolic compounds and reduce oxygen molecules into water molecules. An enzyme production process using fungi through solid fermentation has more advantages compared to the one through submerged fermentation since it has the processing condition as if the fungi grow in nature. This research is aimed at investigating the process of laccase enzyme production by Trichoderma asperellum LBKURCC1 in bioreactor tray through solid state fermentation using rice straw substrates. The objective of this research is to figure out the influence of bed depth and fermenting time on laccase enzyme production by Trichoderma asperellum LBKURCC1. The variables of the research are the bed depth of 1.5, to 4.5 cm and fermentation time of 5, to 10 days. The research findings show that the peak of laccase enzyme activity was obtained at 3.0 cm bed depth and 7 day fermentation time. Increasing the depth of the bed can increase the activity of laccase enzyme produced. However, increasing too much depth of the bed can cause the decrease of laccase enzyme activity. Besides, the fermentation time over 7 days can also decrease the laccase enzyme activity for the amount of the water contained in the bed is drying up.Keywords: bioreactor tray, laccase enzyme, rice straw, Trichoderma asperellum LBKURCC1